On new diagnostic method of gasdischargeplasma - Muratov, M.M.; Ramazanov, T.S.; Dzhumagulova, K.N.; Goree, Jh.A. (Recent Contributions to Physics, 2014)
Plasma with dust particles is considered. In present work a new diagnostic method is proposed. This method allows to calculate and estimate gas discharge plasma parameters on the basis of data obtained from dusty plasma experiments in RF discharge. Pair correlation functions, charge and number density of dust particles are used as data. Method is based on the implementation of sum rules for pair correlation function of dust component. Pair correlation function of dusty plasma is obtained directly from the experiments using video images processing of plasma-dust structure and the analytical method using the pair interaction potential of dust particles. Number densities of electrons and ions in gas discharge plasma were calculatedon the basis of pair interaction potential and pair correlation functions. Theoretical calculation resultsandresults based on the experimental data were compared.Both results obtained through different methods are in good agreement. Thus, the possibility ofusing ofthis method for the diagnostic of plasma in rfdischarge is shown.